IN VITRO STUDIES ON PHYTOCHEMICAL, ANTIOXIDANT, AND ANTIBACTERIAL PROPERTIES OF ADANSONIA DIGITATA L. FRUIT PULP AND LAWSONIA INERMIS L. LEAVES EXTRACTS. - Musab Abdelrahim (Student's Journal of Health Research Africa)
Background